(untitled) (Bangladesh Journal of Neurosurgery, 2024)
Background: Brain abscess is a major health problem with a reasonable morbidity and mortality rate. Objective: The objective of this study was to compare the efficacy between endoscope-assisted evacuations of brain abscess with burr hole aspiration method in a tertiary health care center. Methodology: This non-randomized clinical trial was conducted in the Department of Neurosurgery at Dhaka Medical College Hospital, Dhaka, Bangladesh during the period of July 2016 to December 2017. Patients with the age group of more than or equal to 18 years of both gender presented with brain abscess were enrolled in this study. The endoscope-assisted evacuation of abscess was done on group A patients and burr hole aspiration was done on group B patients. Outcome of the patients was assessed using GCS and MRC muscle power grading and by GOS. Patients were evaluated by contrast enhanced CT scan of head at pre-operative, 1st and 30th postoperative day. Both groups received best available medical treatment along with surgery. Results: The mean age of was 13.0 ± 6.3 years in burr hole group and is 13.1 ± 6.4 years in endoscope-assisted group. The patients presented with GCS was 66.7% in burr hole group and 93.3% in endoscope assisted group. The study showed e”75.0% evacuation of brain abscess at 1st post-operative day in 13(92.9%) patients in endoscope-assisted group and 5(33.3%) patients in burr hole group. The study showed mortality rate of 6.7% in both the groups. Mean residual volume at 30th post operative day was 0.75ml in endoscope-assisted group and 1.75ml in burr hole aspiration group. Conclusion: In conclusion endoscope-assisted procedure has better rate of abscess evacuation, less chance of residual and repeated surgeries than conventional burr hole. Bang. J Neurosurgery 2023; 13(1): 14-19